ANALYSIS OF COVID-19 PANDEMIC INFLUENCES ON NONPERFORMING LOAN IN BANK XYZ FOR THE PERIOD OF 2020-2022 - Pandu Berkatindo MLA; Eko Rizkianto (Dynamic Management Journal, 2023)
This research aims to discuss the influences of the COVID-19 pandemic on nonperforming loan (“NPL”) in Bank XYZ and Bank XYZ’s strategies in responding to it for the period of 2019-2022. This research involves doing an average difference test on the Bank XYZ’s NPL between 1999-2022 and the beginning of pandemic in 2020, so that it can be determined whether the average NPL in 1999-2022 was higher than in 2020. This research was conducted by collecting data through semi-structured in-depth interviews directly to Bank XYZ’s Risk Management Directorate employees and related literature studies. The results of this research suggest that the COVID-19 pandemic had an influences on the increase in NPL at Bank XYZ in 2020, which was reflected in the rise in NPL for debtors, especially debtors with the economic sector affected by the COVID-19 pandemic. Then in 2021 with the strategies implemented, even though it is still in the COVID-19 pandemic, Bank XYZ was able to decrease NPL, when compared to three other state-owned banks and one private bank, the nominal decrease in Bank XYZ's NPL was the largest and was the only one that was below the NPL of banking industry.